Privacy-Preserving Machine Learning: Technological, Social, and Policy Perspectives - Ramadhani, Indri Anugrah; Gunawan, Budi (Digitus : Journal of Computer Science Applications, 2025)
As machine learning and data mining applications increasingly permeate sensitive domains, concerns over data privacy have intensified. This narrative review aims to synthesize current knowledge on privacy-preserving techniques in artificial intelligence, exploring the technological, socio-cultural, and economic-policy dimensions that shape their implementation. The review employed literature from databases including Scopus, IEEE Xplore, and PubMed, using keywords such as "privacy-preserving," "machine learning," and "differential privacy" to select peer-reviewed articles based on defined inclusion and exclusion criteria. The results reveal that differential privacy and federated learning are leading frameworks offering robust solutions for secure computation without compromising analytical performance. Deep learning models demonstrated strong accuracy, particularly when applied to complex datasets such as healthcare records. However, effectiveness is often impeded by systemic issues, including fragmented regulations and uneven infrastructural capacity. Moreover, socio-cultural factors like digital mistrust and limited awareness among users—especially older populations—pose additional barriers. Economic constraints and inconsistent international policy enforcement further complicate adoption across sectors. This review concludes that successful implementation of privacy-preserving technologies depends not only on algorithmic innovation but also on supportive regulatory, cultural, and financial ecosystems. It calls for integrated policy frameworks, targeted public education, and international cooperation to address existing barriers and advance the responsible use of AI in privacy-sensitive applications.